2018
DOI: 10.1007/s00419-018-1394-6
|View full text |Cite
|
Sign up to set email alerts
|

Approximate method for temperature-dependent characteristics of structures with viscoelastic dampers

Abstract: A method for analyzing the influence of temperature on the dynamic characteristics of structures with viscoelastic dampers is proposed in this paper. Dampers which are described by so-called fractional rheological models are considered. The temperature-frequency superposition principle is used to describe the influence of temperature on the dynamic characteristics. The concept of continuous dependence of damping on an artificially introduced parameter is adopted for solving, in an approximate way, the nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…According to equations ( 12) and ( 16), we can obtain s e ¼ α T s or ω e ¼ α T ω (Beheshti andAsadi, 2020, Lewandowski andPrzychodzki, 2018). Finally, equations ( 7) and ( 8) can be rewritten as (Dai et al, 2020;Gai et al, 2020)…”
Section: Time-temperature Correspondencementioning
confidence: 99%
See 1 more Smart Citation
“…According to equations ( 12) and ( 16), we can obtain s e ¼ α T s or ω e ¼ α T ω (Beheshti andAsadi, 2020, Lewandowski andPrzychodzki, 2018). Finally, equations ( 7) and ( 8) can be rewritten as (Dai et al, 2020;Gai et al, 2020)…”
Section: Time-temperature Correspondencementioning
confidence: 99%
“…These results showed that the peak structural responses, including displacement and acceleration, increase with ambient temperature (Beheshti and Asadi, 2020;Chang et al, 1992;Samali and Kwok, 1995). In general, there are three approaches to analyze the ambient temperature effect of VE materials and dampers: by using the thermal-mechanical model (Guo et al, 2016), empirical equation (Chang et al, 1992), and time-temperature correspondence (Beheshti andAsadi, 2020, Lewandowski andPrzychodzki, 2018;Moreira et al, 2010;Wei et al, 2017;Xu et al, 2020). The first is time-consuming when it is applied to a large-scale structure, the second greatly depends on the experimental data, and the third is a widely acceptable method in the polymer viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…In each story, we place one VE damper. Lewandowski (2016), Lewandowski andPawlak (2011), andLewandowski et al (2012) investigated the use of such a controller in different stories.…”
Section: A Four-story Buildingmentioning
confidence: 99%
“…The dynamic analysis of structural components with VE dampers has been the subject of many investigations (Escobedo and Ricles, 1998; Lewandowski, 2016; Lewandowski and Pawlak, 2011; Lewandowski et al, 2012; Singh et al, 2011). The dynamic analysis of a structural system with VE dampers in the state space form has been investigated in Tepljakov (2017) and Chang and Singh (2002).…”
Section: Introductionmentioning
confidence: 99%
“…In [39], the effect of temperature on the dynamic characteristics of beams with a VE layer was investigated experimentally. The authors found the first few non-dimensional damping ratios to decrease with temperature increasing from 5 to 40 • C. Some information concerning the influence of temperature on the dynamic characteristics of structures with VE dampers was presented very recently in the papers [13,41]. Very few papers were also dedicated to the analysis of the influence of temperature on structures with dampers or layers in the time domain.…”
Section: Influence Of Temperature On Dynamic Characteristics Of Strucmentioning
confidence: 99%